‘If this is of God’: Choosing to Curse in Ghanaian Charismatic Christianity - Mark S. Aidoo (Journal for the Study of Religion)
African Christianity takes the challenges from their enemies and the evil forces seriously. There is hardly a call to love the enemy. Moreover, it is about destroying physical or spiritual beings that oppose one’s wellbeing. In the African Pentecostal/Charismatic ministries, one finds pastors and prophets who are cursing their colleagues openly. This essay reflects on the cursing prayers of Bishop Dag Heward-Mills, the founder and Presiding Bishop of Lighthouse Chapel International, and Pastor Kelvin Elson Godson, founder of Zoe Outreach Embassy, Ogbodjo, Accra to explore their religious, ethical, and cultural justifications in contemporary neo-Charismatic ministries in Ghana in light of the African religious and cultural values. It uses the African cultural hermeneutics and paradigmatic approach in biblical ethics to show why the Akan of Ghana do not allow leaders of society to curse others. It shows that it is not only the motive and intention of the one at prayer but also the cultural and religious values that make cursing prayers legitimate or illegitimate.